On the feasibility of secure logging for industrial control systems using blockchain - Schorradt, Stefan; Bajramovic, Edita; Freiling, Felix (ACM International Conference Proceeding Series, 2019)
With industrial control systems (ICSs) being increasingly networked, the need for sound forensic capabilities for such systems increases. One vital source of information in forensic investigation are log files. Techniques for secure logging aim to protect log files from manipulation. We investigate how a blockchain can enable secure logging for ICSs.We argue that a blockchain fits well both into general models of secure logging and into the Purdue model for ICSs. We report on experiences from connecting the syslog functionality of a Siemens SIMATIC S7-1500 programmable logic controller to the public Ethereum blockchain network. While the level of manipulation protection is comparably high, the transaction time for the public Ethereum blockchain severely limits the usefulness of this type of secure logging for ICSs.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Blockchain; Industrial Control Systems Security; Secure Logging